Strategic marketing approaches for enhancing company value through CSR integration - Mandasari, Virginia; Widyah Perdana Putra, Aga (Jurnal Riset Pendidikan Ekonomi, 2024)
This research explores the interplay between Corporate Social Responsibility (CSR), Corporate Value, and Marketing Strategy through the analysis of case studies of five leading companies: Nike, Starbucks, IKEA, TOMS, and Patagonia. Employing a qualitative approach, this study analyzes the business practices of these companies and their relevance to relevant theoretical concepts. The findings indicate that integrating CSR into marketing strategies can strengthen brand image, create long-term value, and build sustainable relationships with customers and other stakeholders. The implications of these findings are crucial for understanding how companies can leverage responsible business practices to achieve long-term success in an increasingly complex business environment.